Eksistensi Pesantren Muhammadiyah Dalam Mencetak Kader Persyarikatan (Studi di Kabupaten Magelang) - Miswanto, Agus (Jurnal Tarbiyatuna, 2019)
This research is about Muhammadiyah boarding schools in Magelang Regency with a qualitative-comparative approach. A comparative approach is used to see two pesantren groups that are different from the management side, namely traditional (salafiyah) and modern (khalaf) pesantren in the Muhammadiyah environment. And to collect data used interview and observation techniques. From this study it was found that Muhammadiyah Islamic boarding schools had readiness to print a cadre of trustees who were well-trained and had advanced Islamic insights. However, in the context of pesantren resources there needs to be improvement and improvement. Of the four pesantren studied. Each has different characteristics both in terms of management and curriculum. In terms of curriculum, pesantren are still searching for the right format, because until now there has been no standard curriculum in the Muhammadiyah boarding school environment. Likewise, the books that have become a handle still have no uniformity between the pesantren.